Data mining on climatic factors for Harumanis mango yield prediction - Rohani S., Mohamed Farook; Abdul Halis, Abdul Aziz; Azmi, Harun; Zulkifli, Husin; Ali Yeon, Md Shakaff, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/